PENGARUH SUNGKUP DAN MULSA TERHADAP PERTUMBUHAN DAN HASIL UMBI BAWANG MERAH (Allium ascalonicum L.) VARIETAS LEMBAH PALU DI DATARAN MEDIUM - T, Moh. Arfan.; Basri, Zainuddin; Fathurrahman, Fathurrahman (AGROTEKBIS, 2016)
This experiment was conducted in Petimbe Village Palolo District Sigi Regency, Central Sulawesi. This experiment used Split Plot Design. The main plot was containment: (N0) = without containment, and (N1) = plastic containment. The subplot was various mulch types: (M0) = without mulching, (M1) = rice straw mulching, (M2) = black plastic mulching, and (M3) = silver plastic mulching. Variables observed were plant height at 40 DAP, the number of leaves at 40 DAP, weight of fresh tuber per clump, the number of fresh tuber per clump and the weight of fresh tubers per five clumps. Result of this experiment showed that plastic containment had a significant effect on the number of leaves (28,38%), but had insignificant effect on plant height. Plastic containment and mulching had a significant effect on the weight gain of fresh tubers per clump (23.50 g) and the weight of fresh tubers per five clumps (12.33 g), but had insignificant effect on the number of fresh tubers per clump. Silver plastic mulching applied with plastic containment resulted in the highest number of tubers (7.47%) compared with without mulching as well as without containment.Â Key Words : Lembah Palu Variety, mulch, Onion, plastic containment.